2010
DOI: 10.1177/0333102409356327
|View full text |Cite
|
Sign up to set email alerts
|

Headache diagnosis, disability and co-morbidities in a multi-ethnic, heterogeneous paediatric Asian population

Abstract: This was a questionnaire survey on headache and migraine prevalence in 2873 Singaporean schoolchildren aged 6 to 16 years. ICHD-II headache classification, disability assessment with PedMIDAS and screening of psychosocial co-morbidities with the Paediatric Symptom Checklist were conducted. Lifetime headache prevalence was high at 80.6%, migraine prevalence was 8.6% and tension headache prevalence was 10.0%. Headache and migraine prevalence was high compared with that found in other Asian studies. Factors signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…1,2 As headache increases in frequency, the impact on children and families can be broad including impairments in school, social, and physical functioning. 1,2 As headache increases in frequency, the impact on children and families can be broad including impairments in school, social, and physical functioning.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As headache increases in frequency, the impact on children and families can be broad including impairments in school, social, and physical functioning. 1,2 As headache increases in frequency, the impact on children and families can be broad including impairments in school, social, and physical functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic influence was described worldwide as well, showing higher headache prevalence among urban, compared to rural population [10,11]. Ethnic differences in headache prevalence were demonstrated in Singapore between Malay and non-Malay ethnicity [12], in Brazil between Caucasians and other ethnicities [13] and in the United States between American Indians, Caucasians and Afro Americans [14]. Jews and Arabs are the two major ethnic groups that comprise the Israeli society.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine affects at least 6% of adolescents in the United States, and chronic daily headache (CDH) estimates for adolescents are as high as 8% worldwide . One large epidemiologic study found that 28% of secondary school students aged 15‐19 suffer from migraine .…”
mentioning
confidence: 99%
“…9,10 Migraine affects at least 6% of adolescents in the United States, and chronic daily headache (CDH) estimates for adolescents are as high as 8% worldwide. 11,12 One large epidemiologic study found that 28% of secondary school students aged 15-19 suffer from migraine. 13 Boys are diagnosed at a younger age, with peak age onset between ages 10 and 14 years, while the peak for girls is later, between ages 14 and 20.…”
mentioning
confidence: 99%